Synthesis of the new 2-[6-Nitro-2-benzothiazolylazo]-4-bromo phenol organic reagent for spectrophotometric determination of Zinc(II). - Jreo, Aqeel Mahdi (Al-Qadisiyah Journal of Pure Science, 2017)
A new 2-[6-Nitro-2-benzothiazolylazo]-4-bromo phenol (NO2BTABrP) organic reagent was synthesized. A sensitive and selective spectrophotometric method was proposed for the rapid determination of Zn(II) using (NO2BTABrP) reagent .The reaction between Zn(II) and (NO2BTABrP) reagent is instantaneous at pH=6.0 and the absorbance remains stable for over 24 hrs. The Method allows for the determination of Zn(II) over the range (0.3-4.0) µg.ml-1 ,with molar absorptivity of (6.221 x 10+3)l.mol ‑1.cm-1 and a detection limit of 0.147 µg.ml-1.Recovery and relative error values of precision and accuracy of method were found to be R.S.D=1.6% , Re=98.84% , and Erel =-1.16% . The properties of complex was studied and show;(M:R) ratio was 1:2 at pH=6.0 ,and the stability constant of 8.23 x 10+9 l2.mol-2 . The interferences of ions (Cu2+ , CrO2- , Ca2+ , pb2+ , Co2+ , Mg2+ , Cd2+, Ba2+ , Bi3+) and masking agents effect on absorbance were studied .